Vertical Farming – The New Era Farming - Sapate, Akash; Singh, Vidya (International Journal of Recent Advances in Multidisciplinary Topics, 2022)
With the expansion in human population and the change in their eating habits. we’ve to vary our traditional farming too; because the population is increasing, we are lacking with the resources. Specially our food resources. Now thanks to urbanization and Land- use conversion we also are face the matter on decreasing of agricultural land. Therefore, we are able to use this technology of vertical farming to attenuate this problem. Vertical farming technology has potential to impact the globe economically, environmentally and socially. We all know because of revolution there was tremendous increase within the agriculture yield production which was led by M. S. Swaminathan in year 1960.vertical farming is that a part of new agriculture revolution. Vertical farming may be a style of indoor farming that seeks to maximize production and efficiency per sq. ft by growing crops in multiple level on a vertical axis. the most aim of this paper is to introduce vertical farming its techniques, methodology, and also the best vertical farming technology using the simplest sustainable technique of agriculture to overcome the problem caused by tradition farming practices and growth. the utilization of specialized purple LED lights enables these crops to grow more efficiently than that of open horizontal farming. By farming inside the building, we will save land use, water, energy, chemicals, and transportation cost too.